Joint user pairing and subchannel allocation for multisubchannel multiuser nonorthogonal multiple access systems - Cheng, Yanyu (2020)
In this paper, we investigate the issues of joint user pairing and subchannel allocation (JUP-SA) in a multisubchannel multiuser nonorthogonal multiple access (NOMA) system. We first investigate the uplink and propose a JUP-SA scheme so that the minimum achievable diversity order of users is maximized. By deriving the upper and lower bounds of the outage probability of the worst-performance user, the achievable diversity order of the scheme is obtained. Following this, the downlink of the system is considered and a JUP-SA scheme that maximizes the minimum diversity order is presented. The closed-form expression of the worst-case outage probability is then derived and validated by simulation results. Numerical results show that both schemes in uplink and downlink NOMA systems can achieve the same diversity order as that of exhaustive search.